Efficient adsorption and photocatalytic degradation of Congo red onto hydrothermally synthesized NiS nanoparticles - Guo, Hongxu (Springer Netherlands, 2013)
NiS nanoparticles (NiS NPs) have been hydrothermally prepared and characterized by the methods of X-ray diffraction, scanning electronic microscope, X-ray photoelectron spectroscopy, UV–Vis diffuse reflectance spectra, photoluminescence, and thermogravimetric analysis. NiS NPs exhibit fast adsorption in the removal of Congo red (CR) in aqueous solution, in which the pseudo-second-order model was the best to describe the adsorption kinetics, and the intraparticle diffusion was not only the rate-limiting step. The NiS NPs also exhibit efficient photocatalytic activity in the degradation of CR under visible-light irradiation, in which the 30 mg/L CR was almost completely degraded after illumination during 210 min. The •OH radicals in the process of photocatalytic degradation were observed by fluorescence technique.